Prognosis of Patients Victim of Spontaneous Subarachnoid Hemorrhage: A Comparison between Radiologic Scales - Hanna, Luiza Maria Dias Abboud; Biguelini, Sarah Eloisa; de Araujo Junior, Francisco Alves; Matsubara, Anderson; dos Santos Neto, Pedro Helo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Objective To analyze the population and the early mortality rate (up to thirty days) of patients victim of spontaneous subarachnoid hemorrhage (SAH) according to the Hunt-Hess clinical scale and the Fisher and modified Fisher radiological scales.Materials and Methods We analyzed 46 medical records and skull computed tomography (CT) scans of patients with spontaneous SAH admitted between February 2014 and December 2017 at Hospital Universitário Evangélico Mackenzie, in the city of Curitiba, state of Paraná, Brazil. The method of the study was exploratory-descriptive, transversal and retrospective, with a quantitative approach. We analyzed epidemiological (gender, age), clinical (life habits, pathologies, Glasgow coma scale and Hunt-Hess scale) and radiological (Fisher and modified Fisher scales) variables, and the Hunt-Hess and the Fisher scales were correlated with risk of death. The data was submitted to statistical analysis considering values of p < 0.05.Result There was a higher prevalence of spontaneous SAH among women (69.5%), as well as among patients aged between 51 and 60 years (34.7%). Regarding the grades on the scales, there was higher prevalence of Fisher 4, Modified Fisher 4 and Hunt-Hess 2. Evolution to death was higher among women (76.4%) and patients aged between 61 and 70 years (35,2%).Conclusion Mortality was higher among patients classified as Fisher 3, Modified Fisher 4 and Hunt-Hess ≥ 3. The Fisher scale is better than the modified Fisher scale to assess the risk of mortality.
Keywords: intracranial vasospasm; subarachnoid hemorrhage; aneurysm; prognosis